A cascade energy cycle based on solid oxide fuel cell with electric energy storage option. Issue 4 (21st December 2022) - Sivaraman, Ramaswamy; Bharath Kumar, Narukullapati; Majdi, Ali; Emad Izzat, Samar; Muda, Iskandar; Molana, Amir
ABSTRACT: Recently, solid oxide fuel cells (SOFCs) have been known as a popular technology due to their versatility in fuel intake, carbon-free process, and scalability in various applications. Besides that, the utilization of their exhaust heat in cascade cycles improves the process behavior by increasing the energy production rate. From the literature, gas turbines (GTs) are typically utilized as the downstream cycle of SOFCs. However, thermionic generators (TIGs) can be integrated with SOFCs in order to utilization the released heat to produce more electric power. TIGs can be more reliable and stable compared to GTs. Moreover, TIG's environmental pollution is significantly lower than GTs. On the other hand, thermoelectric generators (TEGs) are devices that require lower grade heat compared to TIGs. In this study, a conceptual-evaluation study of a SOFC-based cascade cycle integrated with TIG and TEG is presented and discussed under the effective parameters. The introduced cascade system is able to produce electric power to meet consumer demand. In this regard, by using SOFC, the chemical energy of hydrogen is converted into electric power and excess heat under electrochemical reactions. By directing waste heat first to TIG and then to TEG, more electric power is yielded during two processes. Further, when the consumer does not need electricity, electric energy is stored by the hybrid pumped hydro and compressed air system (PHCAS) for later utilization. Therefore, the energy structure introduced in the current article suggests a new arrangement and configuration for electrical energy generation and storage. The outcomes of simulation revealed that the considered structure can produce nearly 3.9 kWh of electric energy per day. The energy efficiency of the system in such a context is almost 69.6%. Moreover, 16.12 moles of hydrogen gas (as fuel of SOFC) are required per hour. Additionally, PHCAS with a volume of nearly 2.98 m 3 is required to store electrical energy. Also, improving the storage performance depends on the use of efficient storage equipment and setting the initial pressure in values close to the peak point.